Anaerobic capacity of sailors with disabilities - Prokopowicz, G.; Molik, B.; Prokopowicz, K.; Ogonowska-Slodownik, A.; Lencse-Mucha, J.; Morgulec-Adamowicz, N.; Kosmol, A.; Perkowski, K.; Chamera, T.; Grzywacz, T. (Polish Journal of Sport and Tourism, 2017)
A review of Polish and international literature does not give a clear indication of the level of anaerobic capacity that sailors with disabilities demonstrate with regard to their functional capacities. This study sought to determine differences in functional capacity levels between sailors from three medical and functional groups. Material and methods. The research was carried outduring a sports camp at the National Sailing Centre in Górki Zachodnie in 2014. Eighteen males with locomotor disabilities were included in the study. The athletes were members of the National Team of Sailors with Disabilities of the Polish Yachting Association. The sportsmen competed in the Skud 18 and 2.4mR Paralympic classes. A 30-second Wingate test for upper limbs was employed in the study. Results. Significant differences in mean power (MP) values were noted between the groups under investigation. The group of wheelchair sailors with improper core stability (A) and the group of wheelchair sailors with proper core stability (B) had significantly lower scores than the group of study participants who were able to move freely, that is to walk (C). Conclusions. The study revealed that a 30-second anaerobic capacity test performed on an arm ergometer differentiated disabled sailors from selected groups in terms of mean power. Research on anaerobic capacity may be used to verify the current classification in Paralympic sailing and will make it possible to differentiate present competition categories.